DIAGNOSIS AND MANAGEMENT OF NEONATAL ESOPHAGEAL ATRESIA: A SYSTEMATIC REVIEW OF CURRENT EVIDENCE - Santos, Raquel Oliveira; Ramos, Beatrice de Lucena; Coutinho, Camila Coutrin; Pereira, Helloá Victoria Sales; Miranda, Marcelly do Nascimento; de Oliveira e Oliveira, Pedro Henrique; de Melo, Rania dos Reis; de Souza, Thaissa Akemy Eda (Seven Editora, 2026)
Neonatal esophageal atresia is characterized by diagnostic complexity and the need for specialized clinical and surgical management, playing an important role in reducing neonatal morbidity and mortality. This study aims to analyze the available evidence regarding the diagnosis and management of esophageal atresia in newborns, emphasizing early identification, timely intervention, and multidisciplinary care. This is a systematic review conducted according to PRISMA recommendations and registered in PROSPERO under number CRD420261361849, with searches performed in the PubMed, LILACS/BVS, and SciELO databases from 2016 to 2026. The findings demonstrated that early diagnosis, especially during the prenatal period, associated with postnatal clinical and radiological confirmation, reduces complications. Furthermore, early surgical management combined with specialized neonatal intensive care contributes to better clinical outcomes and increased survival. It is concluded that the standardization of diagnostic and therapeutic approaches, together with strengthened multidisciplinary care, is essential to improve neonatal prognosis.